2021
DOI: 10.1001/jamanetworkopen.2021.36853
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics, Comorbidities, and Mortality Among Persons Diagnosed With Tuberculosis and COVID-19 in Close Succession in California, 2020

Abstract: Key Points Question What are the sociodemographic, clinical, and epidemiologic characteristics of persons diagnosed with tuberculosis (TB) and COVID-19 in close succession in California? Findings In this cross-sectional analysis of public health surveillance records from California residents, 91 individuals diagnosed with TB and COVID-19 more commonly had Hispanic or Latino ethnicity, diabetes, and residence in a low health equity census tract compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…The difference between the frequency of death among patients with concurrent TB/COVID-19 and TB-alone could not be explained by differences in demographic or clinical characteristics between these groups. Our results are aligned with findings of elevated mortality risk among patients with TB/COVID-19 in California, Asia and South Africa [5][6][7][8]10], and support statements of concern about outcomes for patients with both TB and COVID-19 [2].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The difference between the frequency of death among patients with concurrent TB/COVID-19 and TB-alone could not be explained by differences in demographic or clinical characteristics between these groups. Our results are aligned with findings of elevated mortality risk among patients with TB/COVID-19 in California, Asia and South Africa [5][6][7][8]10], and support statements of concern about outcomes for patients with both TB and COVID-19 [2].…”
Section: Discussionsupporting
confidence: 86%
“…An early multinational study found that while the mortality rate was high among patients with both TB and COVID-19, this could have been the result of older age and other comorbidities in the study population [3,4]. In California, researchers found differences in terms of diabetes prevalence and ethnicity between patients with concurrent TB/COVID-19 and a comparison group of patients who had active TB prior to the COVID-19 pandemic [10]. Surprisingly, the TB-alone and concurrent TB/COVID-19 patient cohorts in NYC were similar to each other in terms of a range of demographic and clinical variables.…”
Section: Comparing Characteristics Of Tb/covid-19 Versus Tb-alone Pat...mentioning
confidence: 99%
“…After testing criteria changed, the prevalence rate increased to approximately 0.06% until 9 June 2020 [ 17 ]. The second study, led by Nabity in 2021, identified 6371 co-infected patients among all California residents between September 3, 2019, and December 31, 2020, resulting in a prevalence rate of approximately 0.02% [ 18 ]. The S3 Table provides detailed information on these two studies.…”
Section: Resultsmentioning
confidence: 99%
“…A notable contribution to the field is a large-scale study led by Nabity in 2021, which provided an updated prevalence rate estimate of approximately 0.02% in California, USA [ 18 ]. In contrast, an earlier study conducted in West Cape Province, South Africa in early 2020 reported a prevalence rate of 0.06%.…”
Section: Discussionmentioning
confidence: 99%
“…The well-documented inequalities in preexisting health conditions, such as diabetes or cardiovascular disease, have been named as core explanatory pathways in adult populations. 16 , 18 , 29 , 30 The risk of a severe clinical course of COVID-19 has been shown to also increase in children if chronic conditions, such as obesity or type 1 diabetes, are present. 31 , 32 At the same time, there is evidence that at least some predisposing diseases (eg, obesity or asthma) may occur more often in children from socioeconomically deprived families.…”
Section: Introductionmentioning
confidence: 99%